Challenges and opportunities in patients with adult congenital heart disease, a narrative review - Fabbri, Matteo; Sahu, Anurag (Frontiers in Cardiovascular Medicine, 2024)
Adult congenital heart disease Pregnancy Transition of care Challenges heart failure